Social sources of disparities in health and health care and linkages to policy, population concerns and providers of care - Graves, William (Advances in library administration and organization, 2009)
How does the disintegration of the Soviet system help us to understand the character of library and information institutions and practices within post-soviet space today? Which aspects of the traditional Soviet 'information order' have disappeared from the contemporary world of libraries and information institutions and which aspects have remained, perhaps to be refigured as critical features of newly emerging national and global projects? This volume brings together diverse reflective essays, reports and empirical analyses of the changing character of the post-soviet library world to address these questions. Individual contributions from Russia, Ukraine, Poland, Czech Republic, Hungary, Bulgaria, Romania, the New Republic of Kosovo, and the post-soviet successor states of Eurasia all provide different perspectives on LIS.